Design as aesthetic education: On the politics and aesthetics of learning environments. (February 2020) - Vagt, Christina
The article, speaking from the double perspective of media history and political aesthetics, discusses the impact of behaviourism and early computer technology on the design of learning environments in the United States after the Second World War. By revisiting B. F. Skinner's approaches to behavioural techniques and cultural engineering, and by showing how these principles were applied first at US design departments, and later to prison education, it argues that cybernetic and behavioural techniques merged in the common field of design and education. Behavioural design of the 1960s and 1970s furthered the cybernetic dream of total control over the world by addressing the learning environment rather than the individual, and operated within a space of possibility that was governed equally by technology and aesthetics. Behavioural design can therefore be understood as a political technology.